Językowy obraz religii i Kościoła katolickiego w publicystyce Jana Hempla (Wiślaka) - Ławrynow, Daria (Slavia Orientalis, 2025)
The main issue discussed in this article is the linguistic view of religion and the Catholic Church in the opinion journalism of Jan Hempel (Wiślak). Hempel published in the Polish left-wing inter-war press ("Myśl Wolna", "Dźwignia", "Nowa Kultura") and the Polish-language Soviet propaganda journal "Bezbožnik Wojujący". The author in analysing the linguistic mechanisms within the creation and pejorativization of the objects, shows Hempel's ideological motivation reflected in verbal layer of text. Hempel mainly used intricated forms of descriptions, epithets and metaphors. He depreciated and desacralized the objects with colloquial, dismissive language, lowercase letters, ironic quotation marks and distancing modalizers. The article reconstructs this pejorative linguistic view of 'ideological enemies'.